Performative Forms of Architecture: from Real Space to Virtual Space (Itinera, 2023)
In this paper we will relate the term «performance» to what, in different ways, can be considered the components of architecture: the project, the body of the dweller, the space itself, the virtual models. The different ways in which each of these elements can «perform» will be analysed in the paragraphs: (1) digital performalism, which redefines the form of the project with new tools; (2) bodies as performative agents in the architectural space; (3) architecture as a place for artistic performances, which can be defined as a performed object, but also as a performing subject; (4) and finally, virtual space, where architecture finds many possibilities of expression, in relation to the bodily performance of the user.
Keywords: philosophy of colour; metaphilosophy; philosophy of art; virtual reality